Sphingolipidomics: qualification and quantification of sphingolipids in yeast - Yücel, Esra Börklü. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
BY4743 parent strain and three homozygous deletion mutants, ino1D/ino1D, slc1D/slc1D and ser2D/ser2D, along with four heterozygous deletion mutants INO1/ino1D, SLC1/slc1D, LCB1/lcb1D, and LCB2/lcb2D of S. cerevisiae are investigated to improve the present knowledge on the synthesis mechanism of sphingolipids in yeast and to qualify as well as to quantify sphingolipid metabolites in S. cerevisiae with an ultimate goal of experimental verification of potential drug targets identified by computational methods. Cells were grown in both rich and minimal media in batch cultivations. ino1D/ino1D mutant, aside from these media, was cultivated in minimal medium without inositol. In batch cultivations of YPD, slc1D/slc1D mutant had overgrown the wild type and ser2D/ser2D mutant had the lowest biomass value among all the strains. In F1 medium, both ino1D/ino1D and slc1D/slc1D mutants had overgrown wild type strain while ino1D/ino1D mutant grown in F1 medium without inositol had the lowest biomass value, 1.78 g/l, among all the biomass values of all strains. Optimum lipid extraction procedure was determined by TLC analysis on silica plates. Commercially available mammalian sphingolipid standards as well as phytoceramide and phytosphingosine standards obtained from yeast were analyzed by HPLC to obtain their retention time values and calibration curves. ser2D/ser2D mutant grown in YPD and ino1D/ino1D mutant grown in F1 without inositol media were the strains with noticeable increases in their phytoceramide levels and decreases in biomass values with respect to wild type strain. However, slc1 /slc1 mutant grown in YPD and F1 media had elevated dihydrosphingosine and phytosphingosine levels as well as biomass values compared to wild type strain. Retention time values of 13.175 min and 16.772 min were proposed to be representing the peaks of MIPC and M(IP)2C, respectively, by analyzing HPLC chromatograms of wild type strain grown in YPD and ino1D/ino1D mutant grown in F1 without inositol media.
Keywords: Yeast.; Sphingolipids.